Five ways to get a grip on organizational logistics, backends, and workflows - Ventrella, Cynthia R; Taifour, Tarek; Rendon, Laura; Donovan, Adamo A (Canadian Medical Education Journal / Revue canadienne de l'éducation médicale, 2022)
Organizational backends and logistics are often complex and many institutions set-up their workflows based on manual and tedious processes that negatively shape their interactions with stakeholders. Incorporating new technologies can be intimidating, however there exists a plethora of financially and technically accessible resources, that don’t require any coding knowledge, that institutions can utilize to enhance their organizational workflow and stakeholder experience. Guided by our own learning experiences in optimal logistical set-up and user design, we wish to highlight five effective and easily implementable tricks to aid higher institutions and student groups in healthcare accomplish their administrative duties.